2020
DOI: 10.1002/cche.10364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growing environment, genotype, and commercial fertilization levels on free asparagine concentration in Western Canadian wheat

Abstract: Background and objectives Free asparagine (ASN) is the precursor to the formation of acrylamide, which is a probable neurotoxic and carcinogenic compound formed during high‐temperature (>120°C) processing of starchy foods, such as cereal‐based products. Controlling the acrylamide concentration of cereal‐based products, for example, bread, within the allowable levels established by the European Commission, is necessary for food safety purposes. One effective measure recommended by the European Commission to mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(39 citation statements)
references
References 45 publications
1
37
1
Order By: Relevance
“…Positive correlations between free asparagine and yield have indeed been found ( Table 3 ) but, perhaps surprisingly, these correlations have not been consistent across studies. Xie et al [ 44 ], for example, found that free asparagine (measured in milligrams per gram of protein) was negatively correlated with grain yield in one year when the yield was low (between two and four tonnes per hectare), but positively associated in another year, when the yield was higher (between four and eight tonnes per hectare), suggesting a non-linear relationship. A reduction in plant stress could explain the negative correlation observed over lower yield values, whilst the positive correlation could be due to greater nitrogen availability in the soil.…”
Section: Relationships Between Free Asparagine Quality and Agronomic ...mentioning
confidence: 99%
“…Positive correlations between free asparagine and yield have indeed been found ( Table 3 ) but, perhaps surprisingly, these correlations have not been consistent across studies. Xie et al [ 44 ], for example, found that free asparagine (measured in milligrams per gram of protein) was negatively correlated with grain yield in one year when the yield was low (between two and four tonnes per hectare), but positively associated in another year, when the yield was higher (between four and eight tonnes per hectare), suggesting a non-linear relationship. A reduction in plant stress could explain the negative correlation observed over lower yield values, whilst the positive correlation could be due to greater nitrogen availability in the soil.…”
Section: Relationships Between Free Asparagine Quality and Agronomic ...mentioning
confidence: 99%
“…For the same wheat samples used in this study, Xie et al (2021) reported that free asparagine was significantly ( p < .0001) affected by E, G, F, and their interactions (G × E, G × F, E × F, and G × E × F). Among these factors, E, G, and G × E had the largest effects on free asparagine content with percent total variances of 44, 31, and 18%, respectively (Xie et al, 2021).…”
Section: Resultsmentioning
confidence: 69%
“…For the same wheat samples used in this study, Xie et al (2021) reported that free asparagine was significantly ( p < .0001) affected by E, G, F, and their interactions (G × E, G × F, E × F, and G × E × F). Among these factors, E, G, and G × E had the largest effects on free asparagine content with percent total variances of 44, 31, and 18%, respectively (Xie et al, 2021). Previous studies in Europe and North America have also shown significant effects of growing conditions, genotype, and fertilization treatments on wheat free asparagine concentration (Corol et al, 2016; Curtis et al, 2009; Ohm et al, 2017).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations